PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. GUNUNG MELAYU (ASIAN AGRI) TERHADAP KESEJAHTERAAN MASYARAKAT DI SEKITAR KEBUN KABUPATEN ASAHAN, SUMATERA UTARA - Resti Pratiwi; Dimas Deworo Puruhito; Ari Astuti (JURNAL ILMIAH AGRITAS, 2022)
Indonesia has vast oil palm plantations. The cultivators also vary, ranging from BUMN to the private sector. One of the private land cultivators is PT. Gunung Melayu (ASIAN AGRI). The company has a Corporate Social Responsibility (CSR) program aimed at the community around the plantation (ring 1). To find out the impact of the program, a research was conducted with the title of Effect of Corporate Social Responsibility (CSR) Program of PT. Gunung Melayu (Asian Agri) Against the Welfare of Communities Around the Plantation. The purpose of this study was to determine the implementation of Corporate Social Responsibility (CSR) PT. Gunung Melayu (Asian Agri) on the welfare of the community around the plantation and its effect on the welfare of the community around the plantation. This study applied a quantitative descriptive method with sampling using the snowball technique and the number of samples of 96 respondents. Data were collected by distributing questionnaires and analyzing data with SPSS 25 for Windows. The results obtained indicate that the CSR program of PT. Gunung Melayu (Asian Agri) has been implemented since 2012. There are three areas around the plantation that have benefited from the CSR program, namely Batu Anam Village, Sidomulyo Village, and Ginting Malaha Village. CSR activities include freshwater fish farming in 2012, renovation of the Aek Sakur bridge in 2012, fostering farmer groups in 2015, construction of a meeting building in 2016, independent smallholder program in 2016, planting trees around the Aek Tarum River in 2017, assistance to the GPI Church's house of worship in 2019, and drilling wells and rehabilitating a prayer room in 2019. From all these programs, it is considered that they have have a significant impact on the welfare of the community around the plantation. This is based on the t-test, showing t-test results of 3.657 with a significance of 0.00 (3,657>1.988).